Concepts of healthy and environmentally sustainable diets clash with a life in transition - findings from a qualitative study in urban Burkina Faso - Fülbert, Hannah; Zoromé, Souleymane; Millogo, Roch Modeste; Danquah, Ina; Herrmann, Alina (Global health action, 2025)
Sub-Saharan African countries like Burkina Faso face a dietary transition and are experiencing a shift in disease burden. We explored perceptions of healthy and environmentally sustainable dietary habits in urban Burkina Faso in order to tailor nutritional interventions to the local population and ultimately improve public and planetary health. We conducted an exploratory qualitative study with semi-structured face-to-face interviews in three informal and two formal neighborhoods of Ouagadougou. The sample comprised 36 adult participants. The interviews were conducted in Mooré and French, audio-recorded, and transcribed verbatim. Data were analysed inductively, using thematic analysis. Participants described their ideal healthy and environmentally sustainable diet as traditional, local, natural, pure, organic, and transparent in terms of food production, processing, and preparation. Perceived barriers to achieve such diets were: limited financial resources, reduced availability of products and limited time for food preparation. Furthermore, participants highlighted discordant food preferences in the family, and a lack of understanding around the interconnection between nutrition, health and the environment as barriers. Most of these barriers were aggravated by the experience of a life in transition due to modernizing lifestyles, globalizing food systems, and a changing environment. Participants’ ideal of a healthy and environmentally sustainable diet clashed with a life in transition. To improve public and planetary health, interventions should aim to empower individuals, alleviate financial constraints, and shape global and local food environments. Main findings: Our participants had clear conceptions regarding healthy and environmentally sustainable diets, yet, the ideal often differed from reality, mainly due to economic barriers.Added knowledge: Unlike quantitative studies that place Burkina Faso at the early stages of the nutrition transition, our participants shared perspectives on changing dietary patterns going along with lifestyle, food system and environmental changes.Global health impact for policy and action: Improving access to healthy and environmentally sustainable diets requires multilevel strategies, including information campaigns, targeted subsidies and taxes, revised national dietary guidelines, and concepts to make local agriculture more climate-resilient. Main findings: Our participants had clear conceptions regarding healthy and environmentally sustainable diets, yet, the ideal often differed from reality, mainly due to economic barriers. Added knowledge: Unlike quantitative studies that place Burkina Faso at the early stages of the nutrition transition, our participants shared perspectives on changing dietary patterns going along with lifestyle, food system and environmental changes. Global health impact for policy and action: Improving access to healthy and environmentally sustainable diets requires multilevel strategies, including information campaigns, targeted subsidies and taxes, revised national dietary guidelines, and concepts to make local agriculture more climate-resilient.